A survey of mental health professionals in a paediatric hospital during COVID-19. (January 2022) - Ching, Brian CF; Bennett, Sophie D; Heyman, Isobel; Liang, Holan; Catanzano, Matteo; Fifield, Kate; Berger, Zoe; Gray, Suzanne; Hewson, Emma; Bryon, Mandy; Coughtrey, Anna E; Shafran, Roz
Background: There is little understanding of the mental health impact for young people with long-term physical health conditions and mental health professionals' experiences of supporting them during COVID-19. This service evaluation aimed to conduct a survey of the psychological services provided by mental health professionals in a paediatric hospital in relation to COVID-19. Method: Clinical psychologists and assistant psychologists ( n = 76) across the hospital were asked to complete a survey, asking about their perceptions of COVID-19's impact on patients and families and experiences of providing support during COVID-19. Open-ended survey questions were analysed qualitatively using framework analysis. Results: Respondents described perceived impacts on patients and families around social isolation, school closure, family relationships, physical health, mental health, treatments and social support. Respondents' experiences of providing mental health support during COVID-19 highlighted themes around providing remote/virtual support, workload and facilitators and barriers to their work. Conclusions: Mental health professionals surveyed reported a complex mental health landscape in young people with long-term physical health conditions and their families during COVID-19. Service-wide involvement is needed to facilitate changes to support vital adaptations to remote/virtual working. Research on the mental health of young people with long-term physical health conditions and staff experiences of providing support is warranted.